Preparation method and application of amphiphilic lignin interfacial compatibilizer
By using amphiphilic lignin interface compatibility agents to improve the interface compatibility of composite films, the problems of insufficient thermal stability, mechanical properties and anti-aging capabilities of existing biodegradable plastic film materials are solved, and high-performance, low-cost and environmentally friendly composite film materials are achieved.
Patent Information
- Application Number
- CN202510066593.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-15
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2045-01-15
AI Technical Summary
Existing biodegradable plastic film materials have problems such as poor thermal stability, low mechanical properties, weak anti-aging ability and high production costs, especially poor interface compatibility affecting the processing and application performance of the material.
An lignin is used as a raw material, and by reacting with alcohol compounds and treating them in deionized water at a specific pH, an lignin interface compatibilities are prepared to improve the interface compatibility between the filler in the composite film and the matrix.
It significantly improves the mechanical properties of composite films, improves its application performance in mulch films, packaging films, vest bags and other fields, and at the same time realizes a low-cost and environmentally friendly production process.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of interface compatibilizers, and in particular to a preparation method and application of an amphiphilic lignin interface compatibilizer. Background Art
[0002] Traditional plastics are non-biodegradable, and the white pollution caused by their widespread use poses a potential threat to human health and the environment. Therefore, biodegradable plastics are gradually regarded as an effective solution to replace traditional non-biodegradable plastics. However, existing biodegradable film materials have many shortcomings, such as poor thermal stability, low mechanical properties, weak anti-aging ability, and high production costs. In order to solve these problems, adding fillers to degradable plastic films has become a common improvement method. However, in the process of adding fillers, poor interfacial compatibility is the biggest bottleneck, which affects the processing performance and final application performance of the material. By introducing interfacial compatibilizers, the interfacial compatibility between fillers and substrates can be effectively improved, thereby improving the processability and applicability of plastics. Traditional interfacial compatibilizers are divided into three categories: hydrophilic, lipophilic, and amphiphilic. Although these interfacial compatibilizers can improve the performance of materials to a certain extent, their modification effects are usually limited, and they may cause harm to the environment during use, which is not in line with the concept of green and sustainable development. Therefore, the development of an interfacial compatibilizer derived from wood biomass is crucial to promote the production of low-cost, high-performance, and green and environmentally friendly biodegradable film materials.
[0003] The purpose of the present invention is to provide an amphiphilic lignin interfacial compatibilizer and a preparation method and application thereof. The compatibilizer of the present invention is used to improve the compatibility between molecules, thereby improving the mechanical properties of the composite film. The method uses lignin as a raw material to prepare the amphiphilic compatibilizer, which enables the composite film to have good mechanical properties while achieving sustainable development. Summary of the invention
[0004] The purpose of the present invention is to provide a preparation method and application of an amphiphilic lignin interfacial compatibilizer, which can significantly improve the interfacial compatibility between two-phase molecules, thereby improving the comprehensive performance of the composite film, so that the composite film can be used in the fields of ground film, packaging film, vest bag, etc.
[0005] To achieve the above-mentioned purpose, the present invention provides a method for preparing an amphiphilic lignin interfacial compatibilizer, comprising the following steps: reacting lignin with an alcohol compound, cooling to room temperature after the reaction, dropping the reactant into deionized water with a pH of 2-7, stirring for 10-60 min, centrifuging, washing, collecting solids, and freeze-drying for 24-96 h to obtain the amphiphilic lignin interfacial compatibilizer.
[0006] Furthermore, the lignin includes one or more of kraft lignin, alkali lignin, organic solvent lignin, DES lignin, ionic liquid lignin, and enzymatic lignin.
[0007] Furthermore, the alcohol compound includes one or more of polyethylene glycol methyl ether methacrylate, polyethylene glycol methyl ether acrylate, polyethylene glycol methacrylate, polyethylene glycol diacrylate, glycerol, ethylene glycol or polyethylene glycol and its derived polyethylene glycol polymers.
[0008] Furthermore, the ratio of lignin to alcohol compounds is 1:10-50 g / g.
[0009] Furthermore, the reaction conditions are: 100-180°C for 1-6 h.
[0010] The present invention also provides a method for preparing a composite film with an amphiphilic lignin interfacial compatibilizer added thereto, which is prepared according to the above-mentioned preparation method and comprises the following steps: Step 1, masterbatch preparation: the dried raw materials are mixed evenly with PBAT, PLA, PHA, PCL or PBS and an amphiphilic lignin interfacial compatibilizer in a high-speed mixer, and the masterbatch is prepared in a twin-screw at 120-170°C; Step 2, hot pressing of the composite film: hot pressing the composite masterbatch at 140-190°C and 2-25 MPa for 1-5 minutes to obtain a composite film; Step 3, blow molding into film, put the masterbatch into a film blowing machine at a temperature of 130-180°C for blow molding into film.
[0011] Furthermore, in step 1, the raw materials include one or more of straw powder, lignin, bamboo powder, wood powder, calcium carbonate, talcum powder, humic acid, and biochar, the mass ratio of the raw materials to PBAT, PLA, PHA, PCL, and PBS is 5:95-70:30, and the amphiphilic lignin interfacial compatibilizer accounts for 1-6% of the total mass of the masterbatch.
[0012] The present invention also provides a composite film with an amphiphilic lignin interfacial compatibilizer added, which is prepared by the above preparation method.
[0013] The present invention also provides an application of a composite film added with an amphiphilic lignin interfacial compatibilizer in ground films, packaging bags and vest bags.
[0014] The advantages and positive effects of the preparation method and application of the amphiphilic lignin interfacial compatibilizer described in the present invention are: 1. The amphiphilic lignin interfacial compatibilizer in the present invention can significantly improve the interfacial compatibility between molecules, thereby improving the mechanical properties of the composite film.
[0015] 2. The raw materials for preparing the amphiphilic lignin interfacial compatibilizer in the present invention are green, low in cost and low in pollution, and are of great significance to sustainable development.
[0016] The technical solution of the present invention is further described in detail below through embodiments. DETAILED DESCRIPTION
[0017] The technical solution of the present invention is further illustrated by the following examples.
[0018] Unless otherwise defined, technical or scientific terms used in the present invention shall have the common meanings understood by one having ordinary skills in the field to which the present invention belongs.
[0019] Unless otherwise defined, the instruments, equipment and reagents used in the present invention are conventionally commercially available.
[0020] Example 1 A composite film with an amphiphilic lignin interfacial compatibilizer added is prepared from 50 parts of PBAT, 50 parts of bamboo powder and 1% of the amphiphilic lignin interfacial compatibilizer.
[0021] 1) 50 parts by weight of bamboo powder; 2) PBAT 50 parts by weight; 3) 1% amphiphilic lignin interfacial compatibilizer.
[0022] The preparation method of the amphiphilic lignin interfacial compatibilizer is as follows: The organic solvent lignin was reacted with ethylene glycol (g / g) at a ratio of 1:10 and 0.01-0.1 g of an acidic catalyst at 100-180 °C for 4-6 h. After the reaction was completed, the mixture was cooled to room temperature and the reactant was dropped into deionized water with a pH of 2-7. The mixture was centrifuged, washed, and freeze-dried for 48 h to obtain an amphiphilic lignin interfacial compatibilizer.
[0023] A method for preparing a composite film with an amphiphilic lignin interfacial compatibilizer added, comprising the following steps: Step 1: 50 parts of bamboo powder, 50 parts of PBAT and 1% of amphiphilic lignin interfacial compatibilizer are taken to prepare masterbatch by twin-screw extrusion. The processing parameters of the twin-screw are as follows: the heating temperature is set to 130-150°C, the roller speed is set to 20-35r / min, and the number of times is 1-5 times.
[0024] Step 2, hot pressing the masterbatch into a film in a hot press to obtain a bamboo powder-based composite film material with an amphiphilic lignin interfacial compatibilizer added. The hot press processing parameters are as follows: the heating temperature is set to 130-155°C, the pressure is set to 1-25 MPa, and the running time is set to 1-5 min.
[0025] Step 3, the masterbatch is blown into a film in a film blowing machine to obtain a bamboo powder-based composite film with an amphiphilic lignin interfacial compatibilizer added. The processing parameters of the film blowing machine are as follows: the heating temperature is set to 130-155°C, and the preheating time is set to 35-50 minutes.
[0026] Example 2 A composite film with an amphiphilic lignin interfacial compatibilizer added is prepared from 50 parts of PBAT, 50 parts of corn straw powder and 3% of the amphiphilic lignin interfacial compatibilizer.
[0027] 1) 50 parts by weight of corn stalk powder; 2) PBAT 50 parts by weight; 3) 3% amphiphilic lignin interfacial compatibilizer.
[0028] The preparation method of the amphiphilic lignin interfacial compatibilizer is as follows: Alkali lignin was reacted with polyethylene glycol (g / g) at a ratio of 1:50 and 0.02-0.1 g of an acidic catalyst at 100-180°C for 6 h. After the reaction was completed, the mixture was cooled to room temperature and the reactant was dropped into deionized water with a pH of 2-7. The mixture was centrifuged, washed, and freeze-dried for 48 h to obtain an amphiphilic lignin interfacial compatibilizer.
[0029] The preparation steps of the composite film are the same as those in Example 1.
[0030] Example 3 A composite film with an amphiphilic lignin interfacial compatibilizer added is prepared from 50 parts of PBAT, 50 parts of cotton straw powder and 4% of the amphiphilic lignin interfacial compatibilizer.
[0031] 1) 50 parts by weight of cotton straw powder; 2) PBAT 50 parts by weight; 3) 4% amphiphilic lignin interfacial compatibilizer.
[0032] The preparation method of the amphiphilic lignin interfacial compatibilizer is as follows: the organic solvent lignin is reacted with ethylene glycol (g / g) at a ratio of 1:20 and 0.01-0.05g of an acidic catalyst at 100-180°C for 6 hours, and after the reaction is completed, the mixture is cooled to room temperature, and the reactant is dripped into deionized water with a pH of 2-7, centrifuged, washed, and freeze-dried for 48 hours to obtain the amphiphilic lignin interfacial compatibilizer.
[0033] The preparation steps of the composite film are the same as those in Example 1.
[0034] Example 4 A composite film with an amphiphilic lignin interfacial compatibilizer added is prepared from 50 parts of PBAT, 50 parts of calcium carbonate powder and 3% of the amphiphilic lignin interfacial compatibilizer.
[0035] 1) 50 parts by weight of calcium carbonate powder; 2) PBAT 50 parts by weight; 3) 3% amphiphilic lignin interfacial compatibilizer.
[0036] The preparation method of the amphiphilic lignin interfacial compatibilizer and the composite film is the same as that in Example 1.
[0037] Example 5 A composite film with an amphiphilic lignin interfacial compatibilizer added is prepared from 50 parts of PBAT, 50 parts of talcum powder and 3% of the amphiphilic lignin interfacial compatibilizer.
[0038] 1) 50 parts by weight of talcum powder; 2) PBAT 50 parts by weight; 3) 3% amphiphilic lignin interfacial compatibilizer.
[0039] The preparation method of the amphiphilic lignin interfacial compatibilizer and the composite film is the same as that in Example 1.
[0040] Comparative Example 1 A bamboo powder-based PBAT composite film is prepared from 50 parts of bamboo powder and 50 parts of PBAT in terms of weight percentage.
[0041] (1) 50 parts by weight of bamboo powder; (2) PBAT 50 parts by weight.
[0042] The method for preparing the composite film comprises the following steps: Step 1: Take 50 parts of bamboo powder and 50 parts of PBAT and prepare masterbatch by twin-screw extrusion. The processing parameters of the twin-screw are as follows: the heating temperature is set to 130-150°C, the roller speed is set to 20-35r / min, and the number of times is 1-5 times.
[0043] Step 2: hot press the masterbatch into a film in a hot press. The hot press processing parameters are as follows: the heating temperature is set to 130-155°C, the pressure is set to 1-25 MPa, and the running time is set to 1-5 minutes.
[0044] Step 3, blow the masterbatch into film in a film blowing machine. The processing parameters of the film blowing machine are as follows: the heating temperature is set to 130~155℃, and the preheating time is set to 35~50min.
[0045] Comparative Example 2 A bamboo powder-based composite film material with a hydrophilic interfacial compatibilizer added is prepared from 50 parts of bamboo powder, 50 parts of PBAT and 3% glycerol.
[0046] (1) 50 parts by weight of bamboo powder; (2) 50 parts by weight of PBAT; (3) 3% glycerol.
[0047] The method for preparing the composite film comprises the following steps: Step 1, take 50 parts of bamboo powder, 50 parts of PBAT and 3% glycerol and prepare masterbatch by twin-screw extrusion. The processing parameters of the twin-screw are as follows: the heating temperature is set to 130~150℃, the roller speed is set to 20~35r / min, and the number of times is 1-5 times.
[0048] Step 2: hot press the masterbatch into a film in a hot press. The hot press processing parameters are as follows: the heating temperature is set to 130-155°C, the pressure is set to 1-25 MPa, and the running time is set to 1-5 minutes.
[0049] Step 3, blow the masterbatch into film in a film blowing machine. The processing parameters of the film blowing machine are as follows: the heating temperature is set to 130~155℃, and the preheating time is set to 35~50min.
[0050] Comparative Example 3 A bamboo powder-based composite film material with an added lipophilic compatibilizer is prepared from 50 parts of bamboo powder, 50 parts of PBAT and 3% of dioctyl phthalate (DOP).
[0051] (1) 50 parts by weight of bamboo powder; (2) 50 parts by weight of PBAT; (3) 3% DOP.
[0052] The method for preparing the composite film comprises the following steps: Step 1, 50 parts of bamboo powder, 50 parts of PBAT and 3% DOP are taken to prepare masterbatch by twin-screw extrusion. The processing parameters of the twin-screw are as follows: the heating temperature is set to 130~150℃, the roller speed is set to 20~35r / min, and the number of times is 1-5 times.
[0053] Step 2: hot press the masterbatch into a film in a hot press. The hot press processing parameters are as follows: the heating temperature is set to 130-155°C, the pressure is set to 1-25 MPa, and the running time is set to 1-5 minutes.
[0054] Step 3, blow the masterbatch into film in a film blowing machine. The processing parameters of the film blowing machine are as follows: the heating temperature is set to 130~155℃, and the preheating time is set to 35~50min.
[0055] Comparative Example 4 A calcium carbonate powder-based composite film is prepared from 50 parts of PBAT and 50 parts of calcium carbonate powder.
[0056] 1) 50 parts by weight of calcium carbonate powder; 2) PBAT 50 parts by weight.
[0057] The method for preparing the composite film comprises the following steps: Step 1: Take 50 parts of calcium carbonate powder and 50 parts of PBAT and prepare masterbatch by twin-screw extrusion. The processing parameters of the twin-screw are as follows: the heating temperature is set to 130-150°C, the roller speed is set to 20-35r / min, and the number of times is 1-5 times.
[0058] Step 2: hot press the masterbatch into a film in a hot press. The hot press processing parameters are as follows: the heating temperature is set to 130-155°C, the pressure is set to 1-25 MPa, and the running time is set to 1-5 minutes.
[0059] Step 3, blow the masterbatch into film in a film blowing machine. The processing parameters of the film blowing machine are as follows: the heating temperature is set to 130~155℃, and the preheating time is set to 35~50min.
[0060] Comparative Example 5 A stone powder-based composite film is prepared from 50 parts of PBAT and 50 parts of talcum powder.
[0061] 1) 50 parts by weight of talcum powder; 2) PBAT 50 parts by weight.
[0062] The method for preparing the composite film comprises the following steps: Step 1: Take 50 parts of talcum powder and 50 parts of PBAT and prepare masterbatch by twin-screw extrusion. The processing parameters of the twin-screw are as follows: the heating temperature is set to 130-150°C, the roller speed is set to 20-35r / min, and the number of times is 1-5 times.
[0063] Step 2: hot press the masterbatch into a film in a hot press. The hot press processing parameters are as follows: the heating temperature is set to 130-155°C, the pressure is set to 1-25 MPa, and the running time is set to 1-5 minutes.
[0064] Step 3, blow the masterbatch into film in a film blowing machine. The processing parameters of the film blowing machine are as follows: the heating temperature is set to 130~155℃, and the preheating time is set to 35~50min.
[0065] The experimental settings of Examples 1-5 and Comparative Examples 1-5 are shown in Table 1: Table 1 Experimental settings
[0066] Performance Testing The performance tests were conducted on the composite films prepared in Examples 1-5 and Comparative Examples 1-5. The tensile strength, elastic modulus and elongation at break are shown in Table 2.
[0067] Table 2 Mechanical properties test results of examples and comparative examples
[0068] After adding the amphiphilic lignin interfacial compatibilizer, the elongation at break of the composite film materials of Example 1, Example 2, Example 3, Example 4 and Example 5 increased to 771.3%, 813.7%, 748.3%, 79.8% and 125.9%, respectively, compared with the composite films without adding the amphiphilic modifier (Comparative Example 1, Comparative Example 4 and Comparative Example 5), which were increased by 18.1%, 24.5%, 14.6%, 56.1% and 9.6%, respectively.
[0069] Example 3 Compared with Comparative Example 1, Example 2 adds an amphiphilic lignin-based interfacial compatibilizer, and the tensile strength, elastic modulus and elongation at break of Example 2 are all improved, indicating that the amphiphilic lignin interfacial compatibilizer can significantly improve the interfacial compatibility of the composite film, thereby improving the mechanical properties of the film.
[0070] Compared with Comparative Examples 2 and 3, Example 3 adds a hydrophilic compatibilizer to Comparative Example 2, a lipophilic compatibilizer to Comparative Example 3, and an amphiphilic lignin interfacial compatibilizer to Example 2. The tensile strength, elastic modulus, and elongation at break of Example 2 are all improved, indicating that compared with the hydrophilic compatibilizer (or lipophilic compatibilizer), the amphiphilic lignin interfacial compatibilizer can significantly improve the interfacial compatibility of the composite film and improve the comprehensive performance of the film. This further proves the effectiveness and excellence of the amphiphilic lignin interfacial compatibilizer.
[0071] Therefore, the present invention adopts the preparation method and application of the above-mentioned amphiphilic lignin interfacial compatibilizer, which can significantly improve the interfacial compatibility between the two-phase molecules, thereby improving the comprehensive performance of the composite film, so that the composite film can be used in the fields of ground film, packaging bags, vest straps or plastic wrap.
[0072] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.
Claims
1. A method for preparing an amphiphilic lignin interfacial compatibilizer, characterized in that: The method comprises the following steps: reacting lignin with an alcohol compound, cooling to room temperature after the reaction is completed, dropping the reactant into deionized water with a pH of 2-7, stirring for 10-60 minutes, centrifuging, washing, collecting solids, and freeze-drying for 24-96 hours to obtain an amphiphilic lignin interfacial compatibilizer.
2. The method for preparing an amphiphilic lignin interfacial compatibilizer according to claim 1, characterized in that: The lignin includes one or more of kraft lignin, alkali lignin, organic solvent lignin, DES lignin, ionic liquid lignin, and enzymatic lignin.
3. The method for preparing an amphiphilic lignin interfacial compatibilizer according to claim 1, characterized in that: The alcohol compound includes one or more of polyethylene glycol methyl ether methacrylate, polyethylene glycol methyl ether acrylate, polyethylene glycol methacrylate, polyethylene glycol diacrylate, glycerol, ethylene glycol or polyethylene glycol and polyethylene glycol-derived polymers thereof.
4. The method for preparing an amphiphilic lignin interfacial compatibilizer according to claim 1, characterized in that: The ratio of lignin to alcohol compounds is 1:10-50 g / g.
5. The method for preparing an amphiphilic lignin interfacial compatibilizer according to claim 1, characterized in that: The reaction conditions are: 100~180℃ for 1-6 h.
6. An amphiphilic lignin interfacial compatibilizer, characterized in that: Prepared according to the preparation method according to any one of claims 1 to 5.
7. A method for preparing a composite film by adding an amphiphilic lignin interfacial compatibilizer, characterized in that: The following steps are involved: Step 1, masterbatch preparation: the raw materials and PBAT, PLA, PHA, PCL or PBS and the amphiphilic lignin interfacial compatibilizer are uniformly mixed in a high-speed mixer, and the masterbatch is prepared in a twin-screw at 120-170°C; Step 2, hot pressing of the composite film: hot pressing the composite masterbatch at 140-190°C and 2-25 MPa for 1-5 minutes to obtain a composite film; Step 3, blow molding into film, put the masterbatch into a film blowing machine at a temperature of 130-180°C for blow molding into film.
8. The method for preparing a composite film with an amphiphilic lignin interfacial compatibilizer according to claim 7, characterized in that: In step 1, the raw materials include one or more of straw powder, lignin, bamboo powder, wood powder, calcium carbonate, talcum powder, humic acid, and biochar. The mass ratio of the raw materials to PBAT, PLA, PHA, PCL or PBS is 5:95-70:30, and the amphiphilic lignin interfacial compatibilizer accounts for 1-6% of the total mass of the masterbatch.
9. A composite film with an amphiphilic lignin interfacial compatibilizer added, characterized in that: Prepared according to the preparation method according to claim 7 or 8.
10. Use of the composite film with an amphiphilic lignin interfacial compatibilizer as claimed in claim 9 in ground film, packaging bag, vest bag and cling film.
Citation Information
Patent Citations
Lignin / starch / PBAT composite film material and preparation method and application thereof
CN115819814A
Lignin-based biodegradable film material as well as preparation method and application thereof
CN118185253A
Plastic compound and preparation process
EP3233995A1
Reactive extrusion processes
US20150259369A1
Method for producing lignin modified with expoxidized soybean oil, and biodegradable polymeric composite comprising modified lignin
WO2021015333A1
Cited By
High-toughness wood-plastic composite material based on carboxyl functionalized ionic liquid modified lignin and preparation method of high-toughness wood-plastic composite material
CN120944138A